2009
DOI: 10.1007/s11060-009-9948-7
|View full text |Cite
|
Sign up to set email alerts
|

Phase II trials of erlotinib or gefitinib in patients with recurrent meningioma

Abstract: There are no established treatments for recurrent meningioma when surgical and radiation options are exhausted. The epidermal growth factor receptor (EGFR) is often over-expressed in meningiomas and may promote tumor growth. In open label, single arm phase II studies of the EGFR inhibitors gefitinib (NABTC 00-01) and erlotinib (NABTC 01-03) for recurrent malignant gliomas, we included exploratory subsets of recurrent meningioma patients. We have pooled the data and report the results here. Patients with recurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
106
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 172 publications
(108 citation statements)
references
References 22 publications
1
106
1
Order By: Relevance
“…A recent systematic analysis proposed a PFS-6 rate of 26% as the benchmark for historical comparisons. 14 Considering this benchmark, hydroxyurea, octreotide analogues, gefitinib, and erlotinib were deemed ineffective, 4,13,16 while anti-angiogenic drugs, including bevacizumab, vatalanib, and sunitinib showed potential activity, with PFS-6 rates of 37.5% to 64.3%. 11,14,17 -19 Interestingly, our data support a potential role of anti-angiogenic treatment in recurrent WHO grades II and III meningioma, as the most pronounced decrease of tumor growth rates was observed in patients put on bevacizumab therapy.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic analysis proposed a PFS-6 rate of 26% as the benchmark for historical comparisons. 14 Considering this benchmark, hydroxyurea, octreotide analogues, gefitinib, and erlotinib were deemed ineffective, 4,13,16 while anti-angiogenic drugs, including bevacizumab, vatalanib, and sunitinib showed potential activity, with PFS-6 rates of 37.5% to 64.3%. 11,14,17 -19 Interestingly, our data support a potential role of anti-angiogenic treatment in recurrent WHO grades II and III meningioma, as the most pronounced decrease of tumor growth rates was observed in patients put on bevacizumab therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Gefitinib, erlotinib, and imatinib, which target platelet-derived growth factor receptor (PDGFR) and epidermal growth factor receptor (EGFR), respectively, have generally been ineffective for AM and MM. 56,66,82 Although imatinib in combination with hydroxyurea did achieve a modest effect in Grade II and III meningiomas with a 6-month PFS of 46%, the 12-month PFS was only 8%. 66 Several authors have suggested antiangiogenic agents for the treatment of AM and MM.…”
Section: Chemotherapymentioning
confidence: 99%
“…Pa-tients with these refractory tumors typically have a median overall survival of only 6-33 months. 9,38,56 Modern trials have looked at the possible utility of receptor tyrosine kinase (RTK) inhibitors. Gefitinib, erlotinib, and imatinib, which target platelet-derived growth factor receptor (PDGFR) and epidermal growth factor receptor (EGFR), respectively, have generally been ineffective for AM and MM.…”
Section: Chemotherapymentioning
confidence: 99%
See 2 more Smart Citations